Silver-Overgrowth-Induced Changes in Intrinsic Optical Properties of Gold Nanorods: From Noninvasive Monitoring of Growth Kinetics to Tailoring Internal Mirror Charges - Tebbe, Moritz; Kuttner, Christian; Mayer, Martin; Maennel, Max; Pazos-Perez, Nicolas; Koenig, Tobias A. F.; Fery, Andreas (Journal of Physical Chemistry C, 2015)
We investigate the effect of surfactant-mediated, asymmetric silver overgrowth of gold nanorods on their intrinsic optical properties. From concentration-dependent experiments, we established a close correlation of the extinction in the UV/vis/NIR frequency range and the morphological transition from gold nanorods to Au@Ag cuboids. Based on this correlation, a generic methodology for in situ monitoring of the evolution of the cuboid morphology was developed and applied in time-dependent experiments. We find that growth rates are sensitive to the substitution of the surfactant headgroup by comparison of benzylhexadecyldimethylammonium chloride (BDAC) with hexadecyltrimethylammonium chloride (CTAC). The time-dependent overgrowth in BDAC proceeds about 1 order of magnitude slower than in CTAC, which allows for higher control during silver overgrowth. Furthermore, silver overgrowth results in a qualitatively novel optical feature: Upon excitation inside the overlap region of the interband transition of gold and intraband of silver, the gold core acts as a retarding element. The much higher damping of the gold core compared to the silver shell in Au@Ag cuboids induces mirror charges at the core/shell interface as shown by electromagnetic simulations. Full control over the kinetic growth process consequently allows for precise tailoring of the resonance wavelengths of both modes. Tailored and asymmetric silver-overgrown gold nanorods are of particular interest for large-scale fabrication of nanoparticles with intrinsic metamaterial properties. These building blocks could furthermore find application in optical sensor technology, light harvesting, and information technology.
CRIS-Team Scopus Importer:2023-03-20